WALIMATUL ‘URS IN ISLAMIC JURISPRUDENCE: CONCEPTS, LEGAL FOUNDATIONS, AND CONTEMPORARY PRACTICES IN MUSLIM SOCIETY - Fahmi Al Munawwar; Muhammad Nasir; Aldiansyah Pane; Zulheddi Zulheddi (Journal Analytica Islamica, 2026)
Walimatul 'Urusy is a tradition recommended in Islam as a form of gratitude and a means of announcing a marriage. This study aims to analyze the concept, legal foundation, and practice of walimatul 'urusy in contemporary Muslim society. The research employs a qualitative approach using a library research method. Data were collected from the Qur'an, Hadith, fiqh books, scholarly books, and relevant journal articles, and were analyzed using a descriptive-analytical method. The findings reveal that walimatul 'urusy holds an important position in Islamic law as a means of publicizing marriage and strengthening social relationships. Its legal basis is derived from the Hadith of Prophet Muhammad (peace be upon him), which encourages the implementation of a wedding feast according to one's capability. In contemporary society, the practice of walimatul 'urusy has undergone various changes due to cultural influences and socio-economic conditions. Therefore, its implementation should remain guided by Islamic principles, emphasizing simplicity, public benefit (maslahah), and avoiding extravagance (israf).